Balinese Customary Law and Tri Hita Karana: A Philosophical Foundation for Sustainable Law in Indonesia - Muthia Sakti (PT. Anagata Sembagi Education, 2025)
This article examines the philosophical significance of Balinese customary law and the Tri Hita Karana principle as a normative foundation for the development of sustainability-oriented law in Indonesia. Using a normative juridical method with statutory and conceptual approaches, the research analyzes legal doctrines, regulatory frameworks, and scholarly discourse to evaluate how Tri Hita Karana contributes to legal philosophy and legal policy. The findings show that Balinese customary law institutionalizes sustainability through spiritual, social, and ecological harmony, demonstrated in resource governance, dispute resolution, family law, economic institutions, and tourism regulation. The study identifies the potential of Tri Hita Karana to shape a national sustainability legal framework through cultural-philosophical integration, strengthening community-based legal institutions, and harmonizing legislation with ethical responsibility to nature and culture. The article concludes that Tri Hita Karana offers a culturally grounded philosophical paradigm capable of enriching national legal development for environmental, social, and cultural sustainability